Goldilocks and the three vampires : a graphic novel - Sutton, Laurie S, 1953- (Far out fairy tales., 2017)
In this graphic adaptation of the fairy tale, Goldilocks is an explorer who searches the world for artifacts and treasures--but when she stumbles on the home of three vampires she has to use all of her skills to navigate the tomb's traps and get out into the sunlight alive.